Analisa Pengembangan Produk Wisata Berdaya Saing dan Berkelanjutan di Kampung Wisata Pintu Kota Kecil, Pulau Lembeh, Kota Bitung - Arthur Lumataw; Mex Usmeny Pesik (PolimdoSains, 2023)
Tourism villages are actually a form of special interest tourism that is comprehensively packaged so that tourists can fully interact with nature, the surrounding community, including local culture and traditions. Pintukota Kecil Tourism Village is located on Lembeh Island, precisely in Batukota Village, Environment II, Bitung City, North Sulawesi Province. This tourist village is partly coconut plantation land and partly beautiful dense forest which is usually used for hiking by foreign guests Implementation becomes an important thing to measure the extent of the success of a program, so that at this stage there needs to be supervision and evaluation in order to achieve the goals that have been set together. Community development activities are activities that aim to develop a certain group in an area that wants to be developed. Community development is commonly known as community empowerment. The main product of a destination related to what can be seen and done by tourists in the tourist village. Attractions can be in the form of natural beauty, local community culture, game facilities and so on. The construction of a bagang (live fish container) accompanied by space for tourists to catch available fish, with the condition that the fish caught by tourists become the property of tourists after being weighed and paid according to the agreed price, so that Pintu Wisata Kota Kecil Village has the characteristics of fishing tourism